Understanding Water Security at Local Government Level in South Africa - Meissner, Richard; Funke, Nikki; Nortje, Karen; Steyn, Maronel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book provides unique insights into the complex issue of water security in South Africa. Based on qualitative research conducted through face-to-face structured interviews and focus group discussions with individuals, traditional leaders, municipal officials, researchers, businesspeople and farmers in the two local governments - the Sekhukhune District and eThekwini Metropolitan Municipalities - it focuses on the peoples' understanding of the concept of water security and whether they believe that the municipalities have achieved water security for all. The research is supported by water security-related statistics, particularly those pertaining to water quality and quantity, and an extensive literature review for the concept of water security. In addition to assessing the state of water security in both municipalities, the book presents a new water security definition and typology, and offers valuable recommendations for future research.
Chapter 1. Water Security and South Africa -- Chapter 2. An Analysis of International and South African Discourses and Perspectives on Water Security -- Chapter 3. The Perceived State of Water Security in the Greater Sekhukhune District Municipality and the eThekwini Metropolitan Municipality -- Chapter 4. Beyond Water Quality and Quantity: A Typology towards Understanding Water Security in South Africa -- Chapter 5. Towards an Individual-centred Water Security Theory.
Keywords: Environment; Physical geography; Water; Hydrology; Environmental policy; Economic development; Environmental Sciences; Physical Geography; Water; Environmental Policy; Development Studies